Dwell time variability at Tanjung Perak Port: A cargo flow analysis based on terminal operators - Syamsuddin, Muhammad Anshar; Purwana, Aditya Subur; Majid, Ilham (Educoretax, 2025)
Ports play a strategic role in supporting the smooth flow of national logistics and trade. Tanjung Perak Port in Surabaya is one of Indonesia's primary harbors. A key performance metric for ports is Dwell Time (DT). This study aims to analyze the variability of Dwell Time at Tanjung Perak Port, adopting a cargo flow approach segmented by terminal operator. Utilizing descriptive quantitative methods and a linear model, the research analyzes secondary data from the National Single Window Institute (LNSW) for the period January 2025 to September 2025. The analytical results indicate that DT variability at Tanjung Perak is significantly influenced by the stages of cargo/container handling at each terminal operator, specifically from stacking to gate-out. For the TPS terminal operator, the distribution of dwell times for the stages of stacking-to-job order, job order-to-gate in, and gate in-to-gate out is right-skewed. Conversely, for the TTL terminal operator, the overall DT and stacking-to-job order distributions are right-skewed, while the job order-to-gate in and gate in-to-gate out times exhibit minimal variability and are relatively uniform. A pronounced right skew indicates a mean value greater than the median, suggesting that while most data points cluster around lower times, significant outliers with extended durations are present. The linear model confirms that these operational stages have a statistically significant influence on overall Dwell Time.